Toxicity and antitumor potential of Mesosphaerum sidifolium (Lamiaceae) oil and fenchone, its major component - Thaísa Leite Rolim; Déborah Ribeiro Pessoa Meireles; Tatianne Mota Batista; Tatyanna Kelvia Gomes de Sousa; Vivianne Mendes Mangueira; Renata Albuquerque de Abrantes; João Carlos Lima Rodrigues Pita; Aline Lira Xavier; Vicente Carlos Oliveira Costa; Leônia Maria Batista; Marcelo Sobral da Silva; Marianna Vieira Sobral (BMC, 2017)
Abstract Background The essential oil from Mesosphaerum sidifolium (L'Hérit.) Harley & J.F.B.Pastore (syn. Hyptis umbrosa), Lamiaceae (EOM), and its major component, have been tested for toxicity and antitumor activity. Methods EOM was obtained from aerial parts of M. sidifolium subjected to hydro distillation, and gas chromatography-mass spectrometry was used to characterize the EOM chemical composition. The toxicity was evaluated using haemolysis assay, and acute toxicity and micronucleus tests. Ehrlich ascites carcinoma model was used to evaluate the in vivo antitumor activity and toxicity of EOM (50, 100 and 150 mg/kg), and fenchone (30 and 60 mg/kg) after 9 d of treatment. Results The EOM major components were fenchone (24.8%), cubebol (6.9%), limonene (5.4%), spathulenol (4.5%), β-caryophyllene (4.6%) and α-cadinol (4.7%). The HC50 (concentration producing 50% haemolysis) was 494.9 μg/mL for EOM and higher than 3000 μg/mL for fenchone. The LD50 for EOM was approximately 500 mg/kg in mice. The essential oil induced increase of micronucleated erythrocytes only at 300 mg/kg, suggesting moderate genotoxicity. EOM (100 or 150 mg/kg) and fenchone (60 mg/kg) reduced all analyzed parameters (tumor volume and mass, and total viable cancer cells). Survival also increased for the treated animals with EOM and fenchone. For EOM 150 mg/kg and 5-FU treatment, most cells were arrested in the G0/G1 phase, whereas for fenchone, cells arrested in the S phase, which represents a blockage in cell cycle progression. Regarding the toxicological evaluation, EOM induced weight loss, but did not induce hematological, biochemical or histological (liver and kidneys) toxicity. Fenchone induced decrease of AST and ALT, suggesting liver damage. Conclusions The data showed EOM caused in vivo cell growth inhibition on Ehrlich ascites carcinoma model by inducing cell cycle arrest, without major changes in the toxicity parameters evaluated. In addition, this activity was associated with the presence of fenchone, its major component.